2010
DOI: 10.1063/1.3299714
|View full text |Cite
|
Sign up to set email alerts
|

rf linewidth reduction in a quantum dot passively mode-locked laser subject to external optical feedback

Abstract: International audienceThe effect of external optical feedback on an InAs/GaAs quantum dot passively mode-locked laser is investigated. The rf linewidth narrows from 8 KHz in the free-running situation to a value as low as 350 Hz under relatively low feedback. The rf linewidth characterization under resonant feedback at a multiple of the laser cavity length validates the prediction of a previous numerical simulation. It is also confirmed that the integrated rms timing jitter varies as the square root of the rf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 13 publications
9
29
0
Order By: Relevance
“…A major limitation of MLLs for most practical applications is their very high timing jitter and phase noise, as spontaneous emission noise and cavity losses make MLLs prone to broad linewidths and, therefore, substantial phase noise [4]. To improve the timing jitter, several experimental methods such as single-cavity feedback [5][6][7][8], coupled optoelectronic oscillators [9], injection locking [10][11][12], and dual-loop feedback [13][14][15] have been proposed and demonstrated. Of the stabilization techniques demonstrated to date, optical feedback is a promising approach in which an additional reflector creates a compound cavity with a high quality factor, with no need for an external radio frequency (RF) or optical source.…”
mentioning
confidence: 99%
“…A major limitation of MLLs for most practical applications is their very high timing jitter and phase noise, as spontaneous emission noise and cavity losses make MLLs prone to broad linewidths and, therefore, substantial phase noise [4]. To improve the timing jitter, several experimental methods such as single-cavity feedback [5][6][7][8], coupled optoelectronic oscillators [9], injection locking [10][11][12], and dual-loop feedback [13][14][15] have been proposed and demonstrated. Of the stabilization techniques demonstrated to date, optical feedback is a promising approach in which an additional reflector creates a compound cavity with a high quality factor, with no need for an external radio frequency (RF) or optical source.…”
mentioning
confidence: 99%
“…Following these predictions, experimental results have shown that the integer resonant configuration can dramatically improve the noise performance of the device. [12][13][14] Concurrently, the sensitivity of a QDMLL to external optical feedback can be of critical importance, depending on whether the application demands insensitivity or a high degree of sensitivity to external perturbation. 15 In this Letter, we report on the external feedback-sensitivity of a two-section passive QDMLL, highlighting the role of the absorber bias voltage as a control parameter to interactively tune the response of the device to applied optical feedback.…”
mentioning
confidence: 99%
“…[12][13][14] Measurements were performed under the long external cavity length (ECL) regime, so that the product of the relaxation frequency f r (a few GHz), and the external cavity round-trip time s ($120 ns) is much greater than 1. All measurements were performed under the nearly resonant case (where the ECL is about an integer multiple of the laser cavity length), keeping the optical delay condition fixed at 0 ps (setting for maximum stability).…”
mentioning
confidence: 99%
“…Some of these sources are gain, cavity length, refractive index and random fluctuations. These random fluctuations are due to fundamental noise sources, such as spontaneous emission, in addition to technical noise sources, such as cavity-length fluctuations [15].…”
Section: Passive Modementioning
confidence: 99%